APPLICATION OF TEACHING THE 1ST LAW OF "THERMODYNAMICS" TO ISOPROCESSES IN SECONDARY SCHOOLS - Razakov Jasur (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, IX graders of general education schools. In order to eliminate the problems and shortcomings in the teaching of the first law of thermodynamics from physics, information is presented using a methodical approach.